Effect of Funding Source on “Spin” in Studies of Ocriplasmin Therapy for Vitreomacular Traction and Macular Hole - Hubschman S (Dove Medical Press, 2020)
Sasha Hubschman, 1 Michael J Venincasa, 1 Ajay E Kuriyan, 2 Jayanth Sridhar 1 1Department of Ophthalmology, Bascom Palmer Eye Institute, Miller School of Medicine, University of Miami, Miami, FL, USA; 2Department of Ophthalmology, Flaum Eye Institute, University of Rochester Medical Center, Rochester, NY, USACorrespondence: Jayanth SridharBascom Palmer Eye Institute, 900 NW 17 th Street, Miami, FL 33136, USATel +1305-326-6124Fax +1305-326-6417Email jsridhar1@med.miami.eduPurpose: To examine the relationship between industry funding and “spin” in randomized controlled trials (RCTs) and meta-analyses investigating use of ocriplasmin for patients with vitreomacular traction (VMT) and macular hole (MH).Methods: In this study, we examined all PubMed and Ovid MEDLINE RCTs and meta-analyses published in journals with impact factor ≥ 2 investigating effectiveness of ocriplasmin use for VMT and MH. The main outcome measure was correspondence between the studies’ main statistical outcome and their abstract conclusion wording. Each article was reviewed by three independent observers and was evaluated for source of funding, industry co-authorship, study methodology, statistical significance of main outcome measure, correspondence between results of main outcome measure and abstract conclusion, and journal impact factor. Funding was determined by public disclosure. Discrepancies were resolved by consensus.Results: Twelve studies met inclusion criteria, of which 11 were industry funded and 1 was non-industry funded; 11 (91.67%) showed correspondence between outcome and abstract conclusion, without difference between industry-funded and non-industry funded publications or between publications in journals with high impact factor (≥ 3) versus low impact factor (≥ 2 and < 3).Conclusion: In RCTs and meta-analyses of ocriplasmin for VMT and MH, our results suggest that neither industry funding nor journal impact factor affected the rate of “spin” in study conclusions. This study helps physicians understand what challenges they face when learning about a newer, less-established drug.Keywords: ocriplasmin, microplasmin, vitreolysis, vitreomacular traction, macular hole, spin